Local knowledge to enhance wildlife population health surveillance: Conserving muskoxen and caribou in the Canadian Arctic. (January 2018) - Tomaselli, Matilde; Kutz, Susan; Gerlach, Craig; Checkley, Sylvia
Abstract: Monitoring and surveillance of wildlife populations, including demographics and health, is often challenging, particularly in resource-constrained and remote settings. However, in areas characterized by subsistence oriented societies, the users of renewable resources hold a vast and holistic ecological knowledge about the natural environment. This knowledge can be instrumental for understanding and early detection of changes in wildlife populations. Using qualitative research methods and participatory epidemiology techniques we documented the local knowledge from resource users of the community of Iqaluktutiaq (Nunavut, Canada) to assess the health and population status and trends for muskoxen and caribou in the area. Semi-structured individual interviews, followed by group interviews, were implemented with 38 participants, and research findings were summarized and then verified with 31 interviewees. Local knowledge identified major declines in the number of muskoxen and caribou in the study area that were corroborated by subsequent aerial population estimates for both species. Observations made by participants allowed inference of possible mechanisms for the recent population declines, including poor recruitment, poor body condition, and increased morbidity and mortality (including endemic and emerging diseases). Engaging resource users in the process of knowledge generation was useful to identify further research priorities and fostered trust among parties that facilitated the subsequent collaborative development of management plans for these species. We use our experience to illustrate that local knowledge contributes to a holistic understanding of wildlife health and can serve as an early warning system to detect changes in wildlife populations. These participatory approaches are portable to other species and settings and can enhance conservation and co-management efforts for wildlife species worldwide.